The travel motives of outbound Chinese tourists - Otafiire, Elly; Lin, Wenhe; Blažević, Marko (The Business of Tourism, 2019)
Tourism in China remained a mere theory until 1970s when China opened its borders to the world. It is at this stage that tourism was recognized by China’s Government as a sector that could bring in foreign exchange and quicken the development process of China. As China opened to the world, even the behavior of Chinese people started changing and they started considering travelling to other places as a hobby. All of this was a base for emerging Chinese outbound tourism. This paper uses literature review method to explore what are the main factors fueling Chinese outbound tourists. Nature, history and cultural similarities are some of the motives singled out by the research, which proved to be only some of the factors motivating Chinese outbound tourists.